Assessment of buffer zone for aquatic organisms in pesticide application - Yarpuz Bozdogan, Nigar (International Journal of Agricultural and Biological Engineering, 2016)
In pesticide applications, the buffer zone helps to protect water sources against pesticide contamination. In 2014, in the Adana province, the percentage of herbicides used was approximately 12% in corn, sunflower, soybean and cotton. To control the weeds, fifteen active ingredients (a.i.) were used in these crops in 2014. These a.i. were acetochlor, aclonifen, benfluralin, bromoxynil, clethodim, dicamba, fluazifop-p-butyl, foramsulfuron, linuron, mesotrione, nicosulfuron, oxyfluorfen, prometryn, trifluralin and tritosulfuron. The aim of this study was to assess the risk of these herbicides on aquatic organisms and estimate buffer zone distances for the above agricultural crops in herbicide application. Risk index (RI) values were calculated according to German Drift Model (GDM) and Dutch Drift Model (DDM). Consequently, buffer zone needs for herbicide application of five a.i., namely acetochlor, benfluralin, linuron, prometryn, and trifluralin, were determined in this study. Results showed that acetochlor a.i. has the highest risk to aquatic organisms and needs a buffer zone distance of more than 57 meters in sunflower cultivation. It was assessed that buffer zone distances should be more than 1.32 m for linuron in soybean, 3.5 m for benfluralin in sunflower, 4.13 m for prometryn (1.5 kg a.i./hm2) in sunflower and 4.19 m for trifluralin in cotton and soybean, and 5.54 m for prometryn (2.0kg a.i./hm2) in cotton. There was no need for a buffer zone in corn.Keywords: buffer zone, pesticide, herbicide, risk index, cotton, sunflower, corn, soybeanDOI: 10.3965/j.ijabe.20160905.2364Citation: Yarpuz-Bozdogan N. Assessment of buffer zone for aquatic organisms in pesticide application. Int J Agric & Biol Eng, 2016; 9(5): 227－234.